Genetic predisposition and hematopoietic malignancies in children: Primary immunodeficiency - van der Werff ten Bosch, Jutte; van den Akker, Machiel (European journal of medical genetics, 2016)
It is assumed that patients with some forms of primary immunodeficiency (PID) have a markedly increased risk of cancer as compared to the healthy population. This increased incidence is seen in children as well as adult patients. The type of malignancy depends on the underlying genetic defect, but hematopoietic cancers are most frequent in almost any subtype of PID. In some patients, a malignancy can even be the first or only symptom of an underlying genetic defect. The possibility of an underlying PID is important for the pediatric oncologist as this might influence the treatment. Also, patients with a known PID should be screened for the occurrence of cancer. It is therefore important to raise awareness on this subject among clinicians involved in the treatment of children with cancer as well as in the treatment of children with PID.